Pelatihan Metode Langsung (Direct Method) dalam Pembelajaran Connected Speech di SMK Kota Batam - Afriana, Afriana; Ambalegin, Ambalegin; Tewarat, Sipri Hanus; Irawan, Nafdi (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2025)
This community service program aims to enhance the speaking fluency of vocational school students through the application of the Direct Method in teaching connected speech. Connected speech, a crucial aspect of natural English pronunciation, is often neglected in conventional English instruction. The Direct Method, which emphasizes immersive language use and oral interaction without translation, was chosen to improve students’ spontaneous speaking skills. The training was conducted at SMK Tunas Muda Batam with 19 students participating in a series of interactive sessions. Using qualitative-descriptive methods, pre-training and post-training observations, along with feedback, were analyzed. Results show a significant increase in students’ confidence, listening comprehension, and ability to produce reduced forms such as linking, assimilation, and elision. This activity highlights the effectiveness of the Direct Method in helping EFL learners internalize natural English rhythm and speech patterns.